2018
DOI: 10.1044/2017_jslhr-h-17-0082
|View full text |Cite
|
Sign up to set email alerts
|

Talker Differences in Clear and Conversational Speech: Perceived Sentence Clarity for Young Adults With Normal Hearing and Older Adults With Hearing Loss

Abstract: Perceived clarity varies widely among talkers, but nearly all produce clear speech that sounds significantly clearer than their conversational speech. Few differences were seen between OHI and YNH listeners except the effect of talker gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Studies have shown that pitch variation and range contribute to speech intelligibility both in quiet and in noise (e.g., Bunton et al, 2001;Laures & Weismer, 1999;Miller et al, 2010). The results of the current study may be in accord with the data from Byrd (1994) and Ferguson (2004), which indicate that females tend to more carefully articulate when recording speech materials, and that the Bclear^speech of females is perceived to have significantly higher clarity than that of male speech (Ferguson & Morgan, 2018). One note of considerable interest is that the male speaker with the highest intelligibility in the current study (76%) was an advanced student in a graduate audiology program who had been trained to speak clearly to listeners with hearing loss.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Studies have shown that pitch variation and range contribute to speech intelligibility both in quiet and in noise (e.g., Bunton et al, 2001;Laures & Weismer, 1999;Miller et al, 2010). The results of the current study may be in accord with the data from Byrd (1994) and Ferguson (2004), which indicate that females tend to more carefully articulate when recording speech materials, and that the Bclear^speech of females is perceived to have significantly higher clarity than that of male speech (Ferguson & Morgan, 2018). One note of considerable interest is that the male speaker with the highest intelligibility in the current study (76%) was an advanced student in a graduate audiology program who had been trained to speak clearly to listeners with hearing loss.…”
Section: Discussionsupporting
confidence: 88%
“…The talker with the highest rating from Experiment 1 (Female 4) had an overall rating of 4.64 and the talker with the lowest rating (Male 1) had an overall rating of 2.58. That is a wider range than was found by Ferguson and Morgan (2018), which also had listeners rate intelligibility of male and female speech using a 7-point scale. The highest and lowest rated talkers in that study (when speaking conversationally) were on average 5.1 and 3.42, respectively.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For the minimum speaking effort, the talker was instructed to speak as if she was speaking to one NH listener in a quiet room. For the medium speaking effort, she was instructed to speak as she would to an NH listener in an everyday conversation, and for the maximum speaking effort, she was instructed to speak as if she was talking to a person with a hearing loss ( Ferguson and Morgan, 2018 ). There were 42 sound files (14 consonants × 3 speaking efforts).…”
Section: Experiments 1: Identify Target and Conflicting Frequency And Time Rangesmentioning
confidence: 99%
“…They had normal hearing, which was verified through a pure-tone audiometry test. Each of the 42 sound files was randomly presented five times in quiet via headphones, and each lab member was asked to rate “how clearly the sound was spoken” on a scale from 1 to 7: 1—lowest possible clarity, 2—very unclear, 3—somewhat unclear, 4—midway, 5—somewhat clear, 6—very clear, and 7—highest possible clarity ( Ferguson and Morgan, 2018 ). The lab members made their selections by clicking on the desired category from the graphical user interface and then pressing the “next” key to continue.…”
Section: Experiments 1: Identify Target and Conflicting Frequency And Time Rangesmentioning
confidence: 99%